From Ancient Texts to Maps (and Back Again) in the Digital World. The DigilibLT Project - Borgna, Alice (Revista de Humanidades Digitales, 2017)
Greek and Latin have long played a central role in the intellectual life of the West, but recent statistics indicate this role is now in jeopardy. This paper suggests how the interaction between Classics and Digital Humanities might help to reverse this negative trend: starting from the case-study of DigilibLT, the Digital Library of Late Antique Latin Texts, I will explain some of the process behind building a digital library and show how digital projects of this sort can create a feedback loop that not only revives Classics Programs in universities, but also generates new projects and new receptions of the Classics within digital media.